2014
DOI: 10.1002/per.1936
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits Increasingly Important for Male Fertility: Evidence from Norway

Abstract: We study the relationship between personality traits and fertility using a survey of Norwegian men and women born from 1927 to 1968 (N = 7017 individuals). We found that personality relates to men's and women's fertility differently; conscientiousness decreases female fertility, openness decreases male fertility and extraversion raises the fertility of both sexes. Neuroticism depresses fertility for men, but only for those born after 1956. The lower male fertility in younger cohorts high in neuroticism cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 64 publications
3
50
0
Order By: Relevance
“…Silka and Kiesler (1977) observed that couples who were intending childlessness or were unsure, expressed greater preference for being alone, were less interested in interaction with people and tended to have more solitary occupations. Extraversion has been positively associated with greater probability of parenthood, earlier parenthood, greater likelihood of non-planned pregnancy, and higher number of children overall (Berg et al 2013;Jokela et al 2011;Tavares 2008;Skirbekk and Blekesaune 2013). The related trait of Sociability (Buss and Plomin 1984) has also been positively associated with the probability of having children (Jokela et al 2009).…”
Section: Extraversionmentioning
confidence: 91%
See 2 more Smart Citations
“…Silka and Kiesler (1977) observed that couples who were intending childlessness or were unsure, expressed greater preference for being alone, were less interested in interaction with people and tended to have more solitary occupations. Extraversion has been positively associated with greater probability of parenthood, earlier parenthood, greater likelihood of non-planned pregnancy, and higher number of children overall (Berg et al 2013;Jokela et al 2011;Tavares 2008;Skirbekk and Blekesaune 2013). The related trait of Sociability (Buss and Plomin 1984) has also been positively associated with the probability of having children (Jokela et al 2009).…”
Section: Extraversionmentioning
confidence: 91%
“…Conscientiousness appears relevant only for women, in whom it is associated with fewer children and lower likelihood of unplanned pregnancy (Berg et al 2013;Jokela et al 2011;Skirbekk and Blekesaune 2013). It is also predictive of later childbirth, although Tavares (2008) noted this was not significant after controlling for education.…”
Section: Conscientiousnessmentioning
confidence: 98%
See 1 more Smart Citation
“…Extraversion (typified by activity, sociability and dominance) positively predicts fertility [92], lifetime number of sexual partners and propensity for leaving a relationship [93] and, in Senegalese males, it also predicted polygyny [86]. Conscientiousness seems to decrease fertility, for example, in Norwegian women across 40 years of data [92] and in British panel data [94] conscientious women postponed childbearing.…”
Section: (D) Personalitymentioning
confidence: 99%
“…Conscientiousness seems to decrease fertility, for example, in Norwegian women across 40 years of data [92] and in British panel data [94] conscientious women postponed childbearing. In Finnish data, the association increased in later cohorts and in both sexes [95].…”
Section: (D) Personalitymentioning
confidence: 99%